High-resolution measurements of essential climate variables in the North Sea from the autonomous surface vehicle HALOBATES during RV Heincke cruise HE614 - Gassen, Lisa; Ayim, Samuel M; Bibi, Riaz; Cortés-Espinoza, Edgar Fernando; Holthusen, Lina Aleke; Jaeger, Leonie; Lagemann, Mitja; Lehners, Carola; Ribas-Ribas, Mariana; Wurl, Oliver (PANGAEA, 2024)
The autonomous surface vehicle HALOBATES measured Essential Climate Variables (ECV), such as sea surface temperature (SST) and salinity (SSS), during the RV Heincke cruise HE614 in the German Bight. HALOBATES captured the SST and SSS at seven depths with a high vertical resolution of about 10 cm, from the near-surface layer (NSL) (between 30 and 100 cm) and the sea surface microlayer (SML) (upper millimeter). Conductivity, temperature, and depth (CTD) sensors measured temperature and conductivity (for salinity calculation) via a flow-through system on HALOBATES. Additional temperature sensors were mounted underneath the catamaran to measure in-situ temperature in situ at six depths in the NSL. Salinity was corrected with discrete water samples to remove biases between the sensors. Two data loggers with several meteorological stations on the catamaran captured important weather variables during operation time. The surfactant concentration was measured from discrete samples of SML and 100 cm depth. HALOBATES was operated between 01 March 2023 and 22 March 2023.
Keywords: autonomous surface vehicle; essential climate variables; near sea surface; North Sea; sea surface microlayer; skin layer